Unregistered Marriage and Its Impact on Family Harmony in Kacok Village, Palengaan District, Pamekasan Regency - Ubaidillah Ubaidillah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2026)
This study examines the practice of nikah sirri (unregistered marriage) and its impact on family harmony in Kacok Village, Palengaan District, Pamekasan Regency. The research employs an empirical method with a descriptive qualitative approach, using in-depth interviews, observation, and documentation as data collection techniques. The findings reveal that nikah sirri is widely practiced without official registration at the Office of Religious Affairs (KUA), resulting in a lack of legal recognition and protection for family members. The study identifies several driving factors behind this practice, including economic constraints, premarital pregnancy, polygamy without legal permission, and administrative barriers. In addition, low legal awareness among community members contributes significantly to the persistence of nikah sirri, as many individuals perceive religious validity as sufficient without considering state law requirements. The absence of legal registration has substantial implications for family harmony, particularly in terms of legal uncertainty, vulnerability of women and children, and potential conflicts within the household. This study highlights the gap between formal legal norms and social practices (law in books versus law in action) and emphasizes the need for comprehensive interventions, including legal education, administrative accessibility, and institutional support, to strengthen family harmony and legal compliance in marriage practices.